“Effectiveness of the use of technological tools in learning English as a second language” - Noroña Altamirano, Nicole Milena (2022)
The change of modality in education has had a great impact for both students and teachers, thereby today it is necessary to know about technological tools and their contribution to the teaching-learning process during virtual classes. This research aimed at analyzing the importance of training in the use of technological tools in the learning of English for students in the fifth semester of the Pedagogy of National and Foreign Languages course at the Technical University of Cotopaxi. In addition, this research has a qualitative approach because it is focused on the description of the students' perspectives regarding the effectiveness of technological tools and the blended learning method. The technique applied was the survey and the instrument was the questionnaire which consisted of sixteen open and closed questions with a Likert scale. These questions allowed the researchers to collect information from each of the students because they were designed to investigate their experiences on the effectiveness of technological tools during virtual classes. The findings obtained were transcribed, coded, segmented and graphed. The main findings showed that the application and training of technological tools for teachers and students during virtual classes is an important factor in helping the learning of a second language such as English. Students can interact in a dynamic way with their teacher, which also benefits them during the development of their English skills such as speaking, reading, writing and listening in an easier and faster way. Likewise, technological tools can act as a support for teachers by attracting the students' attention and motivating them to learn.